Procalcitonin Is a Prognostic Marker of Hospital Outcomes in Patients with Critical Limb Ischemia and Diabetic Foot Infection - Marco Meloni; Valentina Izzo; Laura Giurato; Enrico Brocco; Michele Ferrannini; Roberto Gandini; Luigi Uccioli (Journal of Diabetes Research)
Aim. To evaluate the prognostic role of procalcitonin (PCT) in patients with diabetic foot infection (DFI) and critical limb ischemia (CLI). Materials and Methods. The study group was composed of diabetic patients with DFI and CLI. All patients were treated according to a preset limb salvage protocol which includes revascularization, wound debridement, antibiotic therapy, and offloading. Inflammatory markers, including PCT, were evaluated at admission. Only positive values of PCT, greater than 0.5 ng/ml, were considered. Hospital outcomes were categorized as limb salvage (discharge with preserved limb), major amputation (amputation above the ankle), and mortality. Results. Eighty-six patients were included. The mean age was 67.3±11.4 years, 80.7% were male, 95.1% had type 2 diabetes, and the mean diabetes duration was 20.5±11.1 with a mean HbA1c of 67±16 mmol/mol. 66/86 (76.8%) of patients had limb salvage, 7/86 (8.1%) had major amputation, and 13/86 (15.1%) died. Patients with positive PCT baseline values in comparison to those with normal values showed a lower rate of limb salvage (30.4 versus 93.6%, p=0.0001), a higher rate of major amputation (13 versus 6.3%, p=0.3), and a higher rate of hospital mortality (56.5 versus 0%, p<0.0001). At the multivariate analysis of independent predictors found at univariate analysis, positive PCT was an independent predictor of major amputation [OR 3.3 (CI 95% 2.0-5.3), p=0.0001] and mortality [OR 4.1 (CI 95% 2.2-8.3), p<0.0001]. Discussion. Positive PCT at admission increased the risk of major amputation and mortality in hospital patients with DFI and CLI.